Juvenile Hemochromatosis: A Case Report and Review of the Literature - Akiyoshi Takami; Yasuaki Tatsumi; Katsuhisa Sakai; Yasumichi Toki; Katsuya Ikuta; Yuka Oohigashi; Junko Takagi; Koichi Kato; Kazuhisa Takami (MDPI AG, 2020)
Juvenile hemochromatosis (JH), type 2A hemochromatosis, is a rare autosomal recessive disorder of systemic iron overload due to homozygous mutations of HJV (HFE2), which encodes hemojuvelin, an essential regulator of the hepcidin expression, causing liver fibrosis, diabetes, and heart failure before 30 years of age, often with fatal outcomes. We report two Japanese sisters of 37 and 52 years of age, with JH, who showed the same homozygous HJV I281T mutation and hepcidin deficiency and who both responded well to phlebotomy on an outpatient basis. When all reported cases of JH with homozygous HJV mutations in the relevant literature were reviewed, we found-for the first time-that JH developed in females and males at a ratio of 3:2, with no age difference in the two groups. Furthermore, we found that the age of onset of JH may depend on the types of HJV mutations. In comparison to patients with the most common G320V/G320V mutation, JH developed earlier in patients with L101P/L101P or R385X/R385X mutations and later in patients with I281T/I281T mutations.